Crop Residues Mulch as Organic Weed Management Strategy in Maize. Issue 3 (16th December 2015) - Mahmood, Azhar; Ihsan, Muhammad Zahid; Khaliq, Abdul; Hussain, Saddam; Cheema, Zahid Ata; Naeem, Muhammad; Daur, Ihsanullah; Hussain, Hafiz Athar; Alghabari, Fahad
Abstract : Crop residues mulching can be opted for organic and sustainable weed management in maize. A 2‐year field study was conducted to evaluate the influence of different crop residues on weeds dynamics and productivity of maize under semi‐arid conditions. Chaffed herbage (2–3 cm) of four crops viz., sorghum, sunflower, rice, and maize was mixed in different combinations (each crop at a rate of 6 t ha −1 ) and was surface applied as mulch. A weedy check and s‐metolachlor + atrazine application treatments were also established for comparison. Infestation of weeds had a negative impact on maize growth and yield. Nevertheless, surface applied mulches were helpful in suppressing weed pressure and improving maize growth and yield performance. Among different mulching combinations, the rice + sunflower + maize herbage recorded the maximum reductions in density and dry biomass of horse purslane and purple nutsedge compared with weedy check control. Total weeds suppression by this treatment was almost similar with s‐metolachlor + atrazine application. A maximum increment in terms of crop growth rate, total dry matter accumulation and grain yield was observed due to the mulching of rice + sunflower + maize. All the mulching combinations significantly enhanced the quality of maize as compared with weedy check and the sorghum + sunflower + maize was more effective for maize quality. Taking together, the results depicted that crop residue mulches can effectively suppress weed growth along with enhancing growth, yield and quality of maize, suggesting that it can be successfully employed in organic weed management programs in maize. Abstract : Crop residues are a valuable natural resource and can be opted for organic and sustainable weed management. The present study appraises the influence of different crop residues mulches on weeds dynamics and productivity of maize under semiarid conditions. The results depict that particularly the combination rice + sunflower + maize effectively suppresses weeds and enhances growth and yield of maize.